Super Charge Separation and High Voltage Phase in NaxMnO2. (21st October 2018) - Chen, Xi; Wang, Yichao; Wiaderek, Kamila; Sang, Xiahan; Borkiewicz, Olaf; Chapman, Karena; LeBeau, James; Lynn, Jeffrey; Li, Xin
Abstract: Na x MnO2 shows Mn 3+ and Mn 4+ charge separation with the charge stripe ordering upon Na deintercalation at x = 5/8. In this paper it is shown that, surprisingly, at lower Na compositions of 5/8 > x ≥ 1/18 the phase evolution pathway of Na x MnO2 upon Na deintercalation shows a unique phenomenon of super charge separation, where the Mn 3+ and Mn 4+ ions fully charge‐separate into charge superplanes formed by succession of charge stripes in the third dimension. The Mn 3+ superplanes attract Na ions electronically, and dominate the antiferromagnetic interactions in NaMnO2 . Na ions in Mn 3+ superplanes also naturally pillar the MnO2 layers to form the unusual O1 phases with large interlayer distances at x < 1/3, which dominates the unique electrochemical behavior of NaMnO2 . Abstract : Layered Na x MnO2 upon Na deintercalation shows a unique phenomenon of supercharge separation, where Mn 3+ and Mn 4+ ions fully charge‐separate into charge superplanes, leading to novel electronic and magnetic behaviors. Na orderings also pillar the MnO2 layers to form O1 phases with large interlayer distances at low Na compositions, which lead to superior Na ion diffusion and asymmetric charge‐discharge structure evolution.